2007
DOI: 10.1159/000102991
|View full text |Cite
|
Sign up to set email alerts
|

A Ridge Penalized Principal-Components Approach Based on Heritability for High-Dimensional Data

Abstract: Objective: To develop a ridge penalized principal-components approach based on heritability that can be applied to high-dimensional family data. Methods: The first principal component of heritability for a trait constellation is defined as a linear combination of traits that maximizes the heritability, which is equivalent to maximize the family-specific variation relative to the subject-specific variation. To analyze high-dimensional data and prevent overfitting, we propose a penalized principal-components app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Principal components analysis of heritability (Ott and Rabinowitz, 1999) can be used to extract the eigenvector explaining the most heritability (Lange et al, 2004; Wang et al, 2007; Klei et al, 2008). If the number of traits exceeds the number of individuals, as in a typical gene expression experiment, a ridge penalty can be added to prevent overfitting (Wang et al, 2007).…”
Section: Dimension Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal components analysis of heritability (Ott and Rabinowitz, 1999) can be used to extract the eigenvector explaining the most heritability (Lange et al, 2004; Wang et al, 2007; Klei et al, 2008). If the number of traits exceeds the number of individuals, as in a typical gene expression experiment, a ridge penalty can be added to prevent overfitting (Wang et al, 2007).…”
Section: Dimension Reductionmentioning
confidence: 99%
“…If the number of traits exceeds the number of individuals, as in a typical gene expression experiment, a ridge penalty can be added to prevent overfitting (Wang et al, 2007). …”
Section: Dimension Reductionmentioning
confidence: 99%
“…Then we obtain these PCs using the eigenvectors of the generalized eigen system [23]. Due to the high-dimensional and sparse matrices ( p ≫ N ), Wang et al proposed a ridge penalized principal components approach to obtaining the PCs of Heritability to accommodate large number of phenotypes [11]. In his approach one can use either the PCs from multivariate familial covariance matrix (for unstandardized data) or correlation matrix (for standardized data) as proposed by Bilodeau and Duchesne [22].…”
Section: Methodsmentioning
confidence: 99%
“…They showed that the first PCH as a quantitative trait in linkage analysis has a gain in power compared to the standard PCA. Within the PCH framework, Wang et al [11] proposed a ridge penalized PCs based on heritability (PCH λ ) for high dimensional family data by adding a penalty to the subject-specific variation. Oualkacha et al [12] proposed an ANOVA estimator for the variance components for general pedigrees and high dimensional family data using the PCH framework.…”
Section: Introductionmentioning
confidence: 99%
“…Existing methods include principal components analysis (PCA) where for the first component, a i , i = 1 ,…, K are coefficients that maximize the variance of Ỹ ; principal component of heritability (PCH) with coefficients maximizing the total heritability of Ỹ [18] and penalized PCH applicable to high-dimensional data [19, 20]; and principal components of heritability with coefficients maximizing the quantitative trait locus (QTL) heritability (PCQH) of Ỹ [2124], that is, the variance explained by the genetic marker. The PCQH approaches are designed to maximize the individual phenotype variation explained by the genetic marker and thus may be more powerful than PCA and PCH in genetic association studies.…”
Section: Methods For Detecting Association Using Multivariate Phenmentioning
confidence: 99%